(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
In this research, the design, analysis, improvement, and manufacturing of a horizontal axis wind turbine with symmetrical blade section type (NACA 0012) airfoil have been achieved. For better performance and behavior, it is necessary to install some parameters and controlled the others to achieve the best wind turbine performance. Fortran 90 computer programs are used to analyze and calculate the design data as well as compare these data with the results of CFD code. Then the optimization methods Scmitz, betz and lift/drag optimization were used to improve chord and pitch angle for a wind turbine. Turbine blades were drawn by solidwork program, and then this data was transferred to the 3D printer to manufacture the blades. Note that the blades were made of fiberglass material. The results were as follows, where the Cp =0.481 at TSR=7 before optimization and after optimization, the best results were as follows Cp = 0.556 at Schmitz chord optimization and lift/drag twist optimization, Also Cp = 0.53 at Betz chord optimization and lift/drag twist optimization at same TSR.